Granpa Joad - Thomas Hart Benton (artist):::Creator:::::::::::: (2024)
Illustration of Gran-pa Joad refusing to leave the farm. Caption: "Nuthin' a matter with me," Gran-pa said, "I just ain't a-goin'." from The Grapes of Wrath, illustrated by Thomas Hart Benton, a native of eastern Oklahoma, who was assigned to draw archetypal Oklahomans for 20th Century Fox as the studio believed that would make the casting more accurate.